2015
DOI: 10.1186/s12871-016-0238-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pressure-controlled ventilation with volume-controlled ventilation during one-lung ventilation: a systematic review and meta-analysis

Abstract: BackgroundNot only arterial hypoxemia but acute lung injury also has become the major concerns of one-lung ventilation (OLV). The use of pressure-controlled ventilation (PCV) for OLV offers the potential advantages of lower airway pressure and intrapulmonary shunt, which result in a reduced risk of barotrauma and improved oxygenation, respectively.MethodsWe searched Medline, Embase, the Cochrane central register of controlled trials and KoreaMedto find publications comparing the effects of PCV with those of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
3
21
0
1
Order By: Relevance
“…Investigations into the superiority of PCV over volume controlled ventilation in the intraoperative setting to date have had marginal or conflicting results. For example, a recent meta-analysis of six RCTs of thoracic surgery patients reported that the use of PCV during OLV led to lower peak inspiratory pressures (weighted mean difference −4.91 cm H 2 O; P<0.0001) and a higher ratio of partial pressure of oxygen to fractional inspired oxygen concentration (weighted mean difference 11.04; P=0.04), although these differences are unlikely to be clinically significant 108. Small RCTs in laparoscopic bariatric surgery have yielded similar results 109110.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Investigations into the superiority of PCV over volume controlled ventilation in the intraoperative setting to date have had marginal or conflicting results. For example, a recent meta-analysis of six RCTs of thoracic surgery patients reported that the use of PCV during OLV led to lower peak inspiratory pressures (weighted mean difference −4.91 cm H 2 O; P<0.0001) and a higher ratio of partial pressure of oxygen to fractional inspired oxygen concentration (weighted mean difference 11.04; P=0.04), although these differences are unlikely to be clinically significant 108. Small RCTs in laparoscopic bariatric surgery have yielded similar results 109110.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…High airway pressures or tidal volumes during one-lung ventilation can lead to barotrauma and volutrauma in the contralateral lung. Low-pressure controlled one-lung ventilation can relieve such stress [14]. These management decisions should be made in consultation with an anesthesiologist.…”
Section: Resultsmentioning
confidence: 99%
“…However, clinical studies have shown that the extended use of OLV is an independent risk factor for postoperative pulmonary dysfunction [20]. Excessive stretching or repeated opening of lung tissues is an important cause of VILI during OLV [21]. A lung-protective strategy using low Vt along with PEEP during OLV was confirmed to improve postoperative pulmonary dysfunction [6].…”
Section: Discussionmentioning
confidence: 99%